An Anthropometric Measurement Of Cerebral Palsy Children For Developing Product Design - Musdi, Shanat; Nur Nabilah, Wazir; Shahrol, Mohamaddan (IJSTR, 2019)
In ergonomics fields, anthropometric data can be used and applied in product design and used to develop design process. The research was conducted to study application of anthropometric data in product design for children with special needs. The research focused on anthropometric measurement of the children’s hand with cerebral palsy. However, no specific data of cerebral palsy (CP) children in Malaysian that could be obtained. The objective of this research is to apply and analyze an anthropometric database of cerebral palsy children (aged 12 month – 15 years old) for product design. The data analyze is using descriptive statistic method producing mean, percentiles and standard deviation (S.D) value for anthropometric variables. 30 children with cerebral palsy are involved in this study and 19 hand dimensions have been measured. The subject was informed before data collection started, that the study was to develop an anthropometric database which can be used to improve product design or other ergonomic consideration for cerebral palsy. The result of the study will provide guidelines for product design process.